TRAINING AND COUNSELING ON THE IMPORTANCE OF WORK SAFETY IN BBPLK SERANG CITY - Mamay Komarudin; Wahyu Widodo; Irma Nurmala Dewi (International Journal of Engagement and Empowerment, 2021)
A  safe and healthy workplace is what every worker in the company would want.  Therefore,  it is vital that we lecturers from Bina Bangsa University feel called to hold counselling and training on  K3  to prospective workers in Serang City.    Counselling and training aim to reduce accidents due to work to improve the efficiency and productivity of work. Companies in Indonesia, in    general include common concern  about  K3  compared to  other countries. Indonesia  will be difficult to deal with the global market  with these conditions because  it  will  experience  inefficiencies in  labor  utilization  due to low work productivity.  The problems  outlined  earlier  are   attempted to  be  approached    using  pictures  and  props.   The counseling  and  training  on  K3 are expected to    reduce the risk  of   accidents  and  health problems  for prospective  workers  and  the  surrounding community.